1981
DOI: 10.1300/j082v07n01_05
|View full text |Cite
|
Sign up to set email alerts
|

The Child's Home Environment for Lesbian vs. Heterosexual Mothers:

Abstract: Much research on the lesbian experience has focused on assessing differences between lesbian and heterosexual adults. Less effort has been expended in analyzing the home environment of the child in a lesbian household. This study compares samples of lesbian and heterosexual mothers in terms of the home setting provided and the caregiver role vs-à-vis children. Results reveal a less affluent socioeconomic setting for the children of lesbian mothers. A strong child-development orientation was found among lesbian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
4

Year Published

1986
1986
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 0 publications
0
49
0
4
Order By: Relevance
“…The results show that there are no differences in psychological health between lesbian mothers and divorced heterosexual mothers in self-concept (Mucklow & Phelan, 1979;Rand, Graham, et al, 1982), happiness (Rand, Graham, & Rawlings, 1982) and overall adjustment and psychiatric status (Golombok, Spencer, & Rutter, 1983 ). Furthermore, Rand et al (1982) Miller, Jacobsen and Bigner (1981) investigated 34 lesbian and 47 heterosexual mothers, and reported that the former group was more child oriented in disciplinary techniques than the latter group was. Golombok et al (1983) compared the quality of the parent-child relationship measured using a standardized interview.…”
Section: Parental Functioningmentioning
confidence: 92%
See 1 more Smart Citation
“…The results show that there are no differences in psychological health between lesbian mothers and divorced heterosexual mothers in self-concept (Mucklow & Phelan, 1979;Rand, Graham, et al, 1982), happiness (Rand, Graham, & Rawlings, 1982) and overall adjustment and psychiatric status (Golombok, Spencer, & Rutter, 1983 ). Furthermore, Rand et al (1982) Miller, Jacobsen and Bigner (1981) investigated 34 lesbian and 47 heterosexual mothers, and reported that the former group was more child oriented in disciplinary techniques than the latter group was. Golombok et al (1983) compared the quality of the parent-child relationship measured using a standardized interview.…”
Section: Parental Functioningmentioning
confidence: 92%
“…Cognitive functioning. Two studies (Kirkpatrick, Smith, & Roy, 1981;Green, Green, 1978Mucklow & Phelan, 1979Lewis, 1980Hoeffer, 1981Kirkpatrick, 1981Miller, Jacobsen, & Bigner, 1981 Children …”
Section: Child Developmentmentioning
confidence: 99%
“…8,9 Lesbian mothers fall within the range of normal psychologic functioning on interviews and psychologic assessments and report scores on standardized measures of self-esteem, anxiety, depression, and parenting stress indistinguishable from those reported by heterosexual mothers. 10 Lesbian mothers strongly endorse child-centered attitudes and commitment to their maternal roles [11][12][13] and have been shown to be more concerned with providing male role models for their children than are divorced heterosexual mothers. 6,14 Lesbian and heterosexual mothers describe themselves similarly in marital and maternal interests, current lifestyles, and child-rearing practices.…”
Section: Parenting Attitudes and Behavior Personality And Adjustmenmentioning
confidence: 99%
“…Cela est en partie facilité par le fait que ces familles n'ont pas de rôles dictés par les normes liées aux genres. À ce sujet, il est important de signaler que plus de mères hétérosexuelles que de mères lesbiennes restent à la maison (Miller, Jacobsen et Bigner, 1981). L'étude de Tasker et Golombok (1995) comparant des familles hété-rosexuelles et lesbiennes ayant vécu un divorce indique que les jeunes adultes dont la mère est lesbienne décrivent leur relation avec la conjointe de leur mère de façon plus positive que les jeunes de mère hétérosexuelle avec leur beau-père, ce qui est probablement en lien avec l'implication parentale marquée des beaux-parents homosexuels.…”
Section: D'après De Singly Etunclassified